My bread : the revolutionary no-work, no-knead method - Lahey, Jim (W.W. Norton & Company, 2009)
"Inspired by the ancient art of Italian bread making, Jim Lahey developed artisanal bread that takes only a pot to create. The method, which captured worldwide attention, is practically foolproof and allows the home baker to let the dough rise slowly, without any kneading or fuss, and then bake it in a heavy, preheated pot. Lahey also shares the fun of making his inventive recipes for classic breads like the rustic Italian baguette, the stirato, and his famous pizza bianca"--From publisher description.